A study of an integrated management initiative to improve the Berg River, Western Cape, South Africa - Locke, Kent (Department of Environmental and Geographical Science, 2017)
Integrated Water Resource Management (IWRM) is acclaimed as an important paradigm in the sustainable management of water resources. While the logic of IWRM is largely undisputed, it is often criticised for lacking sufficient guidance on its practical implementation. The gap between theory and practice in IWRM is mainly attributed to divergent interpretations of integration and how implementation should be practically pursued in water governance regimes. This research contributes to the on-going discussion around IWRM by investigating an integrated management initiative in the Berg River Catchment, in the Western Cape, South Africa. The Berg River Partnership (BRP) is a collective of government and non-government actors and stakeholders working together in an effort to improve the Berg River. The Berg River is a socially and economically important water system within the region, supporting a number of crucial industries. The Berg River is also under serious environmental stress due to polluted urban runoff, wastewater effluent discharges, agricultural runoff and the presence of alien invasive flora. The Management and Transition Framework (MTF) is adopted in this study as the framework that underpins the structured analysis of the Berg River Partnership, allowing the principles of IWRM to be identified and assessed in the governance structures and processes of the BRP. The study demonstrates how some principles of IWRM are practically implemented within the Berg River Partnership, while confirming some of the limitations of implementing IWRM.